ANALISIS BIAYA PRODUKSI DAN TITIK IMPAS PENGOLAHAN IKAN SALAI PATIN (Kasus Usaha Soleha Berseri di Air Tiris Kampar) - Ramli, M (Jurnal Perikanan dan Kelautan, 2009)
This research aims to detect cost of goods manufactured and break evenpoint ikan salai patin. Also aim to detect acceptances and business.s profits levels.Researches results show cost of goods manufactured ikan salai patin Rp 29.800/kg, fillet salai patin Rp 37.210/ kg, and nugget Rp 879,5/ package. Sale breakeven point as big as Rp 6.542.064, temporary for sale achieves Rp 25.595.000/month, with profit level 4,78%.